Construction of Ethical Decision Making Model of Tax Consultants in Malang - Farhan, Djuni (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study aims to construct an ethical decision-making model for Tax Consultants in Malang City consisting of: ego depletion and machiavellian nature as an independent variable, religiosity as a moderation variable, and ethical decision making as a dependent variable. This research was conducted at the Tax Consultant Office in Malang in November 2023 – January 2024. The population of all Tax Consultant employees in Malang was 364 people, then sampled with random sampling techniques obtained by 191 employees at the Office. Primary data related to research variables are obtained by sending questionnaires directly to via google form. It was further analyzed using moderation double linear regression. However, it was previously tested: validity, reliability, linearity, model feasibility, and classical assumption tests include: multicollinearity, heteroscedasticity, normality. His hypothesis was tested using a t-test with an alpa of 5%. The results of this study prove that ethical decision making is constructed by: first, ego depletion has a significant negative effect on ethical decision making; second, Machiavellian has a significant negative influence on ethical decision making; third, religiosity reinforces the negative influence of ego depletion on ethical decision making; fourth, religiosity reinforces the Machiavellian megative influence on ethical decision making.